Typology of eaters based on conventional and organic food consumption: results from the NutriNet-Santé cohort study. Issue 4 (17th June 2016) - Baudry, Julia; Touvier, Mathilde; Allès, Benjamin; Péneau, Sandrine; Méjean, Caroline; Galan, Pilar; Hercberg, Serge; Lairon, Denis; Kesse-Guyot, Emmanuelle
Abstract: Limited information is available on large-scale populations regarding the socio-demographic and nutrient profiles and eating behaviour of consumers, taking into account both organic and conventional foods. The aims of this study were to draw up a typology of consumers according to their eating habits, based both on their dietary patterns and the mode of food production, and to outline their socio-demographic, behavioural and nutritional characteristics. Data were collected from 28 245 participants of the NutriNet-Santé study. Dietary information was obtained using a 264-item, semi-quantitative, organic FFQ. To identify clusters of consumers, principal component analysis was applied on sixteen conventional and sixteen organic food groups followed by a clustering procedure. The following five clusters of consumers were identified: (1) a cluster characterised by low energy intake, low consumption of organic food and high prevalence of inadequate nutrient intakes; (2) a cluster of big eaters of conventional foods with high intakes of SFA and cholesterol; (3) a cluster with high consumption of organic food and relatively adequate nutritional diet quality; (4) a group with a high percentage of organic food consumers, 14 % of which were either vegetarians or vegans, who exhibited a high nutritional diet quality and a low prevalence of inadequate intakes of most vitamins except B12 ; and (5) a group of moderate organic food consumers with a particularly high intake of proteins and alcohol and a poor nutritional diet quality. These findings may have implications for future aetiological studies investigating the potential impact of organic food consumption.